Transforming growth factor beta 1 null mutation in mice causes excessive inflammatory response and early death. - Kulkarni, A B (1993)
To delineate specific developmental roles of transforming growth factor beta 1 (TGF-beta 1) we have disrupted its cognate gene in mouse embryonic stem cells by homologous recombination to generate TGF-beta 1 null mice. These mice do not produce detectable amounts of either TGF-beta 1 RNA or protein. After normal growth for the first 2 weeks they develop a rapid wasting syndrome and die by 3-4 weeks of age. Pathological examination revealed an excessive inflammatory response with massive infiltration of lymphocytes and macrophages in many organs, but primarily in heart and lungs. Many lesions resembled those found in autoimmune disorders, graft-vs.-host disease, or certain viral diseases. This phenotype suggests a prominent role for TGF-beta 1 in homeostatic regulation of immune cell proliferation and extravasation into tissues.